Assessment of knowledge of cancer and lymphoedema among breast cancer survivors - Krzywonos, Aleksandra; Ochałek, Katarzyna; Krzywonos-Zawadzka, Anna; Pitala, Kamil (Menopause Review/Przegląd Menopauzalny, 2014)
Aim: To evaluate the knowledge of breast cancer and lymphoedema symptoms among mastectomy survivors. Material and methods: The research was carried out in the Centre of Oncology Branch in Cracow. The survey comprised 60 hospitalized patients as well as 30 healthy subjects from the Małopolska region. The scientific method used was a specially designed questionnaire. Results : Women with a history of cancer demonstrate a health-oriented approach. The subjects known as the experimental group perform breast self-examinations, regularly visit a gynaecologist, are aware of the most severe mastectomy complication – lymphoedema, and recognize the impact of physical activity on it. Breast cancer operation survivors have a good knowledge of breast cancer and lymphoedema, however, existing shortcomings in practical issues are worrying. On the contrary, the control group neglects regular check-ups, evaluates its own knowledge as negligible and, most surprisingly, is not interested in the subject of breast cancer and lymphoedema, even though the subjects of the group believe that arm swelling is connected to all types of breast cancer surgeries. Conclusions : Breast cancer survivors have a good knowledge of their disorder but are still lacking some essential information. Respondents from the control group have a limited knowledge in the field of cancer and lymphoedema, are not interested in breast cancer matters and are not encouraged by gynaecologists to perform breast self-examinations. Educational prevention programs should develop a health-oriented approach among all women and emphasize their basic role in therapy.